PEREMPUAN DALAM PUSARAN BUDAYA, POLITIK DAN KEKUASAAN MENAFSIR NARATIF DALAM 2 Samuel 3 – 6 HISTORIS KRISTIS, KRITIK FEMINIS, IDEOLOGI DALAM NARASI KISAH MIKHAL - Doys Ivone (TANGKOLEH PUTAI, 2020)
The dialogue between snake and woman in Genesis 3: 1-6 is often understood as a form of human's inability to against the temptations of snakes which causes man's relationship with God to become distant. Even in some other dogmatic views, it is said that as a result of the fall, the "image and likeness of God" in man gets broken, even though the text never shows that thing. This paper intends to look at Genesis 3: 1-6 through the Carnivalesque concept which was initiated by a modern philosopher, Mikhail M. Bakhtin. In a research method that focuses on literature study, it is found that the Carnivalesque concept emphasizes the element of human encounter with sang liyan as a meaningful form of life. In particular, the Carnivalesque concept also highlights the encounter between groups of the haves not, which has a unique way of communicating that presents connotative meanings, because each spoken language and the body presents its own meaning. This encounter model with symbolic tone and language is used to analyze the conversation between snakes and women. The results obtained in this analysis do not lead to a separation between humans and God, but rather an awareness of the importance of dialogue between God and humans, without being overshadowed by fear, in order to create a better relationship between God and human.